Studies on subterranean amphipod crustaceans of Primory, Russia. Part 1. Three new species of the genus Pseudocrangonyx from springs and other groundwater habitats in far eastern Russia - Sidorov, Dmitry A.; Gontcharov, Andrey A. (Zootaxa, 2013)
Three new species of the subterranean amphipod of the genus Pseudocrangonyx: P. tiunovi sp. nov., P. holsingeri sp. nov., P. sympatricus sp. nov. and male specimen for P. kseniae Sidorov, 2012 from the South Primory, Far East of Russia are described. The species were found in springs and related groundwater habitats of several river systems belonging to the Japan Sea basin. Phylogenetic analysis based on mt-cox1 sequences supported the species distinctness. A key for the South Primory species of Pseudocrangonyx is provided.